Development of almond flour bread recipe - E. S. Smirnova; E. V. Razhina; N. L. Lopaeva; I. M. Khairova; V. N. Sinko; A. V. Shilovtsev (Новые технологии, 2024)
The industry of bakery products that do not contain gluten has not been studied enough, so this topic is gaining popularity among scientists. The subject of the study was the development of a bread recipe using almond flour. Pumpkin puree and dried seaweed Laminaria ochroleuca were selected as additives. To improve the taste characteristics of the product, it was decided to add dietary fiber, which can add value to the finished product. The goal of the work was to develop a bread recipe using almond flour. The research was carried out in several stages: 1. development of a recipe and production of prototypes;2. analysis of organoleptic indicators; 3. carrying out physical and chemical studies (determination of humidity, acidity). To carry out the analysis, instrumental and visual research methods were used. During the experiment, five samples of bread were obtained, four of them with the addition of different concentrations of pumpkin and seaweed puree. The rate of dietary fiber was calculated based on the daily consumption rate. Sample No. 2, made with the addition of pumpkin puree in an amount of 100 g, had the best organoleptic properties. The bread had a pleasant taste and smell characteristic of the added raw materials, a soft and baked crumb, and the presence of pores. Samples of bread with added seaweed had a specific taste and smell, and traces of unkneading. The research results can be used in the baking industry to expand the range of bakery products. The developed bread can become a very useful product, especially for those categories of the population who are deficient in certain components. Also, given that for the majority of the population bread is a commodity of everyday demand, its preparation will be in great demand.